La réussite éducative en formation professionnelle : validation d’un premier questionnaire - Tsakpinoglou, Florence; Véronneau, Marie-Hélène (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Considering the lack of tools for measuring educational success in vocational training, this study aimed to develop and validate a new measure for that purpose. The Questionnaire on Educational Success in Vocational Training (QRÉ-FP) is a 24-item scale that measures educational success by taking into account the three missions of Quebec schools: to educate, socialize, and qualify students. Data collection was conducted in person with 212 francophone students in the Montreal area, including 50 who responded again four weeks later. The QRÉ-FP has strong psychometric properties. Exploratory factor analysis reveals three factors (instruct, socialize, qualify) with satisfactory temporal stability and internal consistency. The confirmatory factor analysis showed good model fit as a function of the three-part model. Self-esteem and self-efficacy are correlated with QRÉ-FP scores. In conclusion, this questionnaire is a useful tool in the context of research and intervention with students in vocational training.